Identifikasi Kandungan Nutrisi Limbah Pertanian Dan Perkebunan Di Provinsi Jambi Sebagai Sumber Bahan Baku Pakan Alternatif - Pangentasari, Dwinda; Nurhayati, Nurhayati; Nelwida, Nelwida; Arfiana, Bs Monica; Lestari, Sekar Yunita; Sagala, Haposan (Jurnal Akuakultur Sungai dan Danau, 2026)
Feed is the largest component of operational costs in cultivation activities, reaching 60-70% of total production costs. However, the current price of feed is still very high due to feed raw materials still being imported. Therefore, efforts are needed to reduce import values by substituting soybean meal with other alternative raw materials. Alternative raw materials can be obtained, one of which is from the utilization of agricultural and plantation waste. This study aims to identify and analyze the nutritional content of agricultural and plantation waste in Jambi Province as a source of alternative fish feed raw materials. This study will be conducted over 6 months in several locations that produce agricultural and plantation waste in Jambi Province. The determination of research areas is done purposively considering that the research locations are sources of agricultural and plantation waste in Jambi Province. Types of agricultural and plantation waste that will be identified covering corn, pineapple, oil palm, rubber, coconut, areca nut, and sugarcane waste. Data collected include the total production of agricultural and plantation products over the past year, estimates of waste from production, identification of potential agricultural and plantation waste based on availability, and analysis of nutrient content (proximate). The research results show the nutrient values of each agricultural and plantation waste covering (protein, fat, fiber, moisture content, ash, and dry matter). Rubber seed waste shows the highest protein and fat values, namely 28.9% and 24.13%. The highest fiber content is found in areca nut husk at 46.45%. The highest moisture and ash content are found in pineapple peel at 77.52% and 4.6%. Meanwhile, the highest dry matter value is found in oil palm at 90.5%.